2021
DOI: 10.3390/ani11082199
|View full text |Cite
|
Sign up to set email alerts
|

L-Asparaginase, Doxorubicin, Vincristine, and Prednisolone (LHOP) Chemotherapy as a First-Line Treatment for Dogs with Multicentric Lymphoma

Abstract: Cyclophosphamide exhibits the weakest therapeutic effect compared with vincristine and doxorubicin in the CHOP (C, cyclophosphamide; H, doxorubicin; O, vincristine; and P, prednisolone) chemotherapeutic protocol for the treatment of canine lymphoma. Twenty dogs with multicentric lymphoma were treated using the LHOP protocol, which used l-asparaginase in place of cyclophosphamide, and the outcomes were historically compared with those of dogs that received CHOP chemotherapy in the same institution. No significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…The outcome for multicentric or generalised nodal lymphoma treated with a CHOP-like protocol was reported in 43 papers with 54 groups and 4382 cases [ 5 , 12 , 13 , 15 , 22 , 38 , 40 , 43 , 55 , 56 , 58 , 64 , 76 , 83 , 85 , 88 , 90 , 92 , 95 , 97 , 98 , 99 , 100 , 102 , 107 , 110 , 111 , 112 , 113 , 118 , 120 , 123 , 124 , 126 , 132 , 134 , 136 , 166 , 168 , 169 , 172 , 174 , 175 ]. Nine papers included only dogs with B-cell lymphoma [ 12 , 13 , 15 , 55 , 56 , 76 , 88 , 102 , 124 ], three included only T-cell lymphoma [ ...…”
Section: Resultsmentioning
confidence: 99%
“…The outcome for multicentric or generalised nodal lymphoma treated with a CHOP-like protocol was reported in 43 papers with 54 groups and 4382 cases [ 5 , 12 , 13 , 15 , 22 , 38 , 40 , 43 , 55 , 56 , 58 , 64 , 76 , 83 , 85 , 88 , 90 , 92 , 95 , 97 , 98 , 99 , 100 , 102 , 107 , 110 , 111 , 112 , 113 , 118 , 120 , 123 , 124 , 126 , 132 , 134 , 136 , 166 , 168 , 169 , 172 , 174 , 175 ]. Nine papers included only dogs with B-cell lymphoma [ 12 , 13 , 15 , 55 , 56 , 76 , 88 , 102 , 124 ], three included only T-cell lymphoma [ ...…”
Section: Resultsmentioning
confidence: 99%
“…Considering the effect of the L-COP protocol on kidney function, while cyclophosphamide has mostly been reported to be related to hemorrhagic cystitis [ 39 ], few studies have reported drug-related nephrotoxicity of cyclophosphamide [ 40 , 41 ]. Although limited information is available, L-asparaginase and vincristine have direct effects on kidney function [ 42 , 43 ]. In contrast, prednisolone has anti-inflammatory effects that improve kidney function and hemodynamic stability [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these patient dogs, cases with ≥2 types of tumors and medical records with limited information were categorized as the “other” group. For dogs with lymphoma, the immunophenotype was determined by flow cytometry or immunohistochemistry 23 . Mast cell tumors (MCTs) were categorized by recorded grade according to the clinical staging system proposed by the World Health Organization (WHO) 24 .…”
Section: Methodsmentioning
confidence: 99%
“…For dogs with lymphoma, the immunophenotype was determined by flow cytometry or immunohistochemistry. 23 Mast cell tumors (MCTs) were categorized by recorded grade according to the clinical staging system proposed by the World Health Organization (WHO). 24 Dogs with regional or systemic metastasis were classified as stage II or above.…”
Section: Patient Selection and Evaluationmentioning
confidence: 99%